PEMANFAATAN MEDIA SOSIAL DALAM UPAYA MENINGKATKAN PENERIMAAN SISWA BARU DI SMA SWASTA - Alifia Habibah; Dian Hidayati (Academy of Education Journal, 2023)
Competition between schools in the world of education is in fact unavoidable. The competition is getting more intense every year given the emergence of many private schools. For private schools, especially at the high school level, the most crucial thing is how to increase public interest, which is expected to have a direct impact on increasing new student admissions at the school. Social media is considered as one of the strategies that has a strong impact in efforts to increase the acceptance of new students in the midst of increasing competition between schools, especially in private high schools which are increasingly emerging lately. This research method is descriptive qualitative. The subjects of this study were 2 people including the head of the new student admissions team in high school, namely the Deputy Head of Public Relations, and the head of a private high school. The object of this research is the school's social media. The results of this study show that various social media are used such as Instagram, Facebook, Twitter, Youtube, and Tiktok. The social benefits in increasing new student admissions are for school promotion media, branding, reaching a wide area more effectively and increasing the interest of prospective students. Social media management must also be considered to maximize the use of social media in increasing new student admissions.